Profiling Anthocyanins in Thai Purple Yams (Dioscorea alata L.) - Subin Srivichai; Parichat Hongsprabhas (International Journal of Food Science)
Two accessions of Thai purple yam (Dioscorea alata) were investigated for their chemical constituents during tuber development when the vines were 3 to 8 months old. Yam tubers contained total phenolic compounds ranging between 100 and 385 mg gallic acid equivalent (GAE), flavonoids 60–160 mg catechin equivalent (CE), monomeric anthocyanin of 10–90 mg cyanidin-3-glucoside equivalent (CGE), 70 g starch, and 25–30 g amylose in 100 g yam tuber on a dried weight basis, depending on the accession and age of yam vine. LCMS-IT-TOF mass spectrometry revealed that anthocyanins in both accessions from 8-month-old vines had cyanidin or peonidin nucleus. Their glycosides were nonacylated, monoacylated, or diacylated with sinapic or ferulic acid. The major yam anthocyanins found in both accessions were alatanin C (cyanidin 3-(6-sinapoyl gentiobioside). This study revealed the insights on chemical components during tuber development and characteristics of alatanins for future selection and cultivation of purple yam tubers.